2009
DOI: 10.1056/nejmoa0807611
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Flow Reserve versus Angiography for Guiding Percutaneous Coronary Intervention

Abstract: Routine measurement of FFR in patients with multivessel coronary artery disease who are undergoing PCI with drug-eluting stents significantly reduces the rate of the composite end point of death, nonfatal myocardial infarction, and repeat revascularization at 1 year. (ClinicalTrials.gov number, NCT00267774.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
2,357
9
107

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,715 publications
(2,527 citation statements)
references
References 37 publications
54
2,357
9
107
Order By: Relevance
“…Various clinical trials demonstrated the benefits of using FFR measurement to more accurately identify stenosis that are obstructive and guide revascularization intervention successfully 11, 12, 23. FFR is currently recommended in clinical guidelines only in stable CAD but the transition from stable to unstable syndromes is a continuum without a clear boundary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various clinical trials demonstrated the benefits of using FFR measurement to more accurately identify stenosis that are obstructive and guide revascularization intervention successfully 11, 12, 23. FFR is currently recommended in clinical guidelines only in stable CAD but the transition from stable to unstable syndromes is a continuum without a clear boundary.…”
Section: Discussionmentioning
confidence: 99%
“…When arteries with stenosis >20% were visually perceived, an FFR pressure wire (Certus, St. Jude Medical, St. Paul, MN) was positioned distal to the stenosis of interest to determine vessel FFR using RadiAnalyzer (St. Jude Medical) under steady‐state hyperemia (intravenous adenosine: 140 μg/kg per minute for 3–6 minutes). FFR ≤0.80 was considered as an evidence‐based physiological threshold indicative of obstructive CAD in clinical practice to perform percutaneous coronary intervention 11, 12…”
Section: Methodsmentioning
confidence: 99%
“…We conservatively considered the upper limit of the small transition zone to limit the number of potentially ischemic lesions left untreated as in the Fractional Flow Reserve versus Angiography for Multivessel Evaluation (FAME) study. 9,10,16 As defined by Poiseuille's law of fluid dynamics, pressure gradient is influenced by coronary blood flow and viscosity, minimum radius, and lesion length. In effect, the pressure gradient is inversely proportional to the fourth power of the lesion radius (r 4 ) and is proportional to lesion length.…”
Section: Discussionmentioning
confidence: 99%
“…Between April 2013 and July 2015, we recruited 42 patients (62±9 years) from routine coronary angiography waiting lists, in 2 distinct groups (Figure 1): Patients with obstructive coronary stenoses (n=32): defined by either a coronary artery stenosis >50% on quantitative coronary angiography15 or fractional flow reserve ≤0.8 16. These patients had typical anginal symptoms and multiple risk factors, or known obstructive coronary artery stenoses awaiting percutaneous coronary intervention.…”
Section: Methodsmentioning
confidence: 99%